2012
DOI: 10.7314/apjcp.2012.13.6.2477
|View full text |Cite
|
Sign up to set email alerts
|

Urothelial Tumors of the Urinary Bladder in Manipur: A Histopathological Perspective

Abstract: The study included 26 cases of transitional cell tumors of urinary bladder. The male to female ratio was 1.5: 1 and the ages ranged from 38 years to 73 years (medians of 60 and 64 years, respectively). Of the total, 14 (53.9%) cases were low grade, 9 (34.6%) were high grade, 2 (7.7%) were papillomas and 1 (3.9%) was a papillary urothelial neoplasm of low malignant potential (PUNLMP). Pathological staging showed that 14 (53.9%) of the cases were stage PTa, four (15.4%) PT1, and eight (30.9%) PT2. Some 18.2% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 12 publications
20
36
1
Order By: Relevance
“…[6] 2004-2005 106 59.4 Zhang et al [7] 2006-2010 658 61.9 Gupta et al [8] 2001-2008 561 60.2 Laishram et al [9] 2001-2010 26 62 Biswas et al [10] 2007-2009 88 65 Present Study 2012-2014 45 59.3 As compared to other study series the present study also showed relatively higher male incidence. The gender incidence in our study was more in males than females with a sex ratio of 3.1:1 which is lower than the most of the studies [7][8] [10] but higher than the study done by Laishram et al [9] [7] 2006-2010 548 110 5:1 Gupta et al [8] 2001-2008 431 50 8.6:1 Laishram et al [9] 2001-2010 15 11 1.5:1 Biswas et al [10] 2007-2009 76 12 6.3:1 Present Study 2012-2014 34 11 3.1:1 In the present study we found that haematuria(80%) was the most common presenting symptom. Other symptoms abdominal pain (9%), increased frequency (5%) and urinary incontinence, vaginal bleeding and amenorrhea (2% each) were noted.…”
Section: Figure 4: Presenting Symptoms Of Urothelial Carcinomasupporting
confidence: 64%
“…[6] 2004-2005 106 59.4 Zhang et al [7] 2006-2010 658 61.9 Gupta et al [8] 2001-2008 561 60.2 Laishram et al [9] 2001-2010 26 62 Biswas et al [10] 2007-2009 88 65 Present Study 2012-2014 45 59.3 As compared to other study series the present study also showed relatively higher male incidence. The gender incidence in our study was more in males than females with a sex ratio of 3.1:1 which is lower than the most of the studies [7][8] [10] but higher than the study done by Laishram et al [9] [7] 2006-2010 548 110 5:1 Gupta et al [8] 2001-2008 431 50 8.6:1 Laishram et al [9] 2001-2010 15 11 1.5:1 Biswas et al [10] 2007-2009 76 12 6.3:1 Present Study 2012-2014 34 11 3.1:1 In the present study we found that haematuria(80%) was the most common presenting symptom. Other symptoms abdominal pain (9%), increased frequency (5%) and urinary incontinence, vaginal bleeding and amenorrhea (2% each) were noted.…”
Section: Figure 4: Presenting Symptoms Of Urothelial Carcinomasupporting
confidence: 64%
“…Therefore, the invasion cannot be assessed. In his study, Laishram et al (5) found muscle invasion in 42.1% cases. (5) Our study showed 25% cases of invasive urothelial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In his study, Laishram et al (5) found muscle invasion in 42.1% cases. (5) Our study showed 25% cases of invasive urothelial carcinoma. Hence, inclusion of detrusor muscle in the cystoscopic biopsy is very important.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations